Effects of Growth-Related Genes on Body Measurement Traits in Wenshang Barred Chickens - Cheng Yang; Jun Teng; Chao Ning; Wenwen Wang; Shuai Liu; Qin Zhang; Dan Wang; Hui Tang (The Journal of Poultry Science, 2022)
Body measurement traits (BMTs), which are classical quantitative traits of vital responses to body growth, have been studied in pigs, cattle, and sheep for several decades. In chickens, BMTs mainly cover body slope length, keel length, chest width, chest depth, tibia length, and tibia diameter; however, their genetic markers are yet to be considered. In this study, the Wenshang Barred chicken, a meat-egg-type native breed in China, was used to investigate the association between BMTs and the expression of growth-related genes, including GH, IGF1, IGF2, GHRL, IGF1R, IGFBP2, GHF-1, and TSHB. The results revealed that the single nucleotide polymorphism (SNP) rs3138025 in GH was significantly associated with keel length (P＝0.0455 <0.05), rs313810945 in IGF2 was significantly correlated with chest width (P＝0.0454 <0.05) and chest depth (P＝0.0259 <0.05), and rs317298536 in TSHB significantly affected chest depth (P＝0.0399 <0.05). The SNPs were associated with traits reflecting body size and were potentially involved in bone growth, which was consistent with studies in humans, rodents, and other vertebrate species. In addition, a borderline significant association was found between rs317298536 and body weight (P＝0.0604). These polymorphic sites may be treated as candidate genetic markers in breeding programs involving Wenshang Barred chickens.